2016
DOI: 10.1080/01490451.2015.1041182
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Transformation in Microbially Mediated Pyrite Oxidation by Acidithiobacillus ferrooxidans: Insights From X-ray Photoelectron Spectroscopy-Based Quantitative Depth Profiling

Abstract: 2015): Sulfur transformation in microbially mediated pyrite oxidation by Acidithiobacillus ferrooxidans: insights from X-ray photoelectron spectroscopy-based quantitative depth profiling, Geomicrobiology Journal, AbstractThe oxidation of pyrite and other sulfides is responsible for the generation of acid mine drainage and acid rock drainage, which leads to further contamination of soil and water. In these processes, microbial oxidation usually prevails over chemical oxidation. To determine the mechanism of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Soil was collected from surface layer of soil up to 6–8 inches, placed in sterilized zipper bags and transferred to Soil and Aquatic Microbiology Lab at Soil and Crop Sciences Department of Texas A&M University. For isolation of targeted microorganisms, the soil sample was enriched with 9K medium 25 supplemented with 1% pyrite and incubated at 25 °C for fifteen days in rotary shaker at 120 rpm. About 50 µl of each enrichment was plated on ferrous tryptic soya agar plates 26 and incubated at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Soil was collected from surface layer of soil up to 6–8 inches, placed in sterilized zipper bags and transferred to Soil and Aquatic Microbiology Lab at Soil and Crop Sciences Department of Texas A&M University. For isolation of targeted microorganisms, the soil sample was enriched with 9K medium 25 supplemented with 1% pyrite and incubated at 25 °C for fifteen days in rotary shaker at 120 rpm. About 50 µl of each enrichment was plated on ferrous tryptic soya agar plates 26 and incubated at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Tested with six pentlandite-bearing sulfide ores, a similar nickel leaching efficiency was achieved at both pH 2.00 and 3.00. Unlike chalcopyrite [28] and pyrite [29], the bioleaching of nickel from pentlandite could be achieved with a lower concentration of Fe 3+ and higher pH value. Most pentlandite-bearing ores are associated with magnesium-bearing silicate gangue mineral such as olivine and serpentine.…”
Section: Implications For Hydrometallurgical Applications In the Nickmentioning
confidence: 99%
“…EDS maps of oxygen showed that elements of oxygen mainly exist in oxides but are scarce in background minerals ( Figure 6H ). These element compositions were akin to the product shapes of pyrite oxide mediated by iron-oxidizing bacteria, such as Acidithiobacillus ferrooxidans ( Li J. et al, 2015 ) and Leptospirillum ferrooxidans ( Harneit et al, 2006 ), and further indicated the iron oxidation function of MM125-6. Together, the functions of autotrophic, iron oxidation and production of exopolysaccharides enable us to explain why the ability of strain MM125-6 grows in oligotrophic modified MMJHS medium and how the genus Alcanivorax adheres to and is active on the surface of iron-rich substrates in various deep sea environments.…”
Section: Discussionmentioning
confidence: 93%